Structural variation and evolution of chloroplast tRNAs in green algae - Qi,Fangbing; Zhao,Yajing; Zhao,Ningbo; Wang,Kai; Li,Zhonghu; Wang,Yingjuan (PeerJ, 2021)
As one of the important groups of the core Chlorophyta (Green algae), Chlorophyceae plays an important role in the evolution of plants. As a carrier of amino acids, tRNA plays an indispensable role in life activities. However, the structural variation of chloroplast tRNA and its evolutionary characteristics in Chlorophyta species have not been well studied. In this study, we analyzed the chloroplast genome tRNAs of 14 species in five categories in the green algae. We found that the number of chloroplasts tRNAs of Chlorophyceae is maintained between 28–32, and the length of the gene sequence ranges from 71 nt to 91 nt. There are 23–27 anticodon types of tRNAs, and some tRNAs have missing anticodons that are compensated for by other types of anticodons of that tRNA. In addition, three tRNAs were found to contain introns in the anti-codon loop of the tRNA, but the analysis scored poorly and it is presumed that these introns are not functional. After multiple sequence alignment, the Ψ-loop is the most conserved structural unit in the tRNA secondary structure, containing mostly U-U-C-x-A-x-U conserved sequences. The number of transitions in tRNA is higher than the number of transversions. In the replication loss analysis, it was found that green algal chloroplast tRNAs may have undergone substantial gene loss during the course of evolution. Based on the constructed phylogenetic tree, mutations were found to accompany the evolution of the Green algae chloroplast tRNA. Moreover, chloroplast tRNAs of Chlorophyceae are consistent with those of monocotyledons and gymnosperms in terms of evolutionary patterns, sharing a common multi-phylogenetic pattern and rooted in a rich common ancestor. Sequence alignment and systematic analysis of tRNA in chloroplast genome of Chlorophyceae, clarified the characteristics and rules of tRNA changes, which will promote the evolutionary relationship of tRNA and the origin and evolution of chloroplast.
Keywords: Chlorophyceae; Chloroplast tRNA; Anticodon; Intron; Evolution